TENDENCIES TO INCREASE THE EFFECTIVENESS OF HISTORY LESSONS (American Journal of Interdisciplinary Research and Development, 2023)
History is an independent social science that has its place at all stages of education and is important in raising a mature generation. This article discusses how to organize historical education more effectively by analyzing national and foreign literature.